PENINGKATAN PRODUKTIVITAS LIMBAH PERTANIAN DAUN BAWANG DAYAK (Eleutherine Palmifolia L. Merr ) SEBAGAI ALTERNATIF KRIM ANTI AGING ALAMI - Eka Kumalasari; Erna Prihandiwati (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Eleutherine palmifolia L. Merr are typical plants of Borneo. Pharmacologically the part tubers are proven to have a therapeutic effect. Eleutherine palmifolia grow in the tropics, one of which is in the Petuk Katimpun area of ​​Palangkaraya, Central Borneo, where there land are vast Eleutherine palmifolia. After harvesting Eleutherine palmifolia will produce agricultural waste in the form of leaves that are not utilized and left to rot. Eleutherine palmifolia leaves waste extract contains flavonoid compounds and has antioxidant potential. Eleutherine palmifolia leaves antioxidants can be used to inhibit the aging of the skin and as an alternative to synthetic antioxidants which are harmful to health. Until now there has been no research that to take advantage of Eleutherine palmifolia leaves waste into active substances in antiaging creams. Therefore it is necessary to conduct research to obtain cream preparations with waste active ingredients as antiaging. Waste extract has a very strong antioxidant activity with an IC50 value of 45.33 ppm. One way ANOVA analysis that all cream had significantly different antioxidant attenuation (p < 0,05). Post Hoc analysis Formula III is a the formula with the damping antioxidant reduction the very biggest that is 63.84% ± 0.0891. From the results of the study, the waste of Eleutherine palmifolia leaves can be used as an alternative to anti-aging creams, which one of the efforts increased productivity of agricultural waste.